Higher prevalence of hypervirulent Klebsiella pneumoniae isolates with high-risk multidrug resistance in Asia - Lin Gan; Pan Mao; Ziyan Tian; Xin Li; Zihui Yu; Bing Du; Guanhua Xue; Chao Yan; Jinghua Cui; Hanqing Zhao; Yanling Feng; Junxia Feng; et al. (Journal of Infection and Public Health)
Background: The emergence of hypervirulent and antibiotic-resistant Klebsiella pneumoniae isolates poses a significant global public health threat, necessitating stringent prevention and control strategies on an international scale. However, current research efforts are often geographically restricted and lack integration of large-scale data analyses, limiting the understanding of the global prevalence and molecular epidemiology of K. pneumoniae. Furthermore, studies on hypervirulent K. pneumoniae (hvKp) have predominantly emphasized virulence traits, with limited exploration of their associations with molecular subtypes, such as sequence types (STs) and capsule types. Methods: To address these gaps, a total of 55,684K. pneumoniae isolates collected across global regions, were applied in this study to investigate virulence factors, antimicrobial resistance profiles, molecular typing characteristics and the intrinsic connections between these features. Results: Through the application of big data analytics, we generated a comprehensive global distribution map of K. pneumoniae, revealing a higher prevalence of hvKp isolates with high-risk multidrug resistance in Asia. Notably, sequence types ST23, ST65, and ST86 exhibited the highest proportions of hvKp isolates. Regional differences in the virulence potential of specific sequence types were associated with the presence of aerobactin, a key siderophore. Additionally, capsular type KL64 was identified as potentially correlated with hypervirulence. Conclusions: This large-scale genomic surveillance offers critical insights into the global distribution and molecular epidemiology of K. pneumoniae, providing an evidence base for risk mapping and the formulation of tailored control strategies to mitigate the threat posed by this pathogen.